1987
DOI: 10.2337/diab.36.12.1414
|View full text |Cite
|
Sign up to set email alerts
|

Na+-K+-ATPase Pumping Activity Is Not Directly Linked to myo-inositol Levels After Sorbinil Treatment in Lenses of Diabetic Rats

Abstract: Changes in tissue levels of sorbitol, myo-inositol, and Na+-K+-ATPase enzyme activity have been implicated in the development of diabetic complications in animal models of the disease and in humans. The ability of the aldose reductase inhibitor sorbinil to reverse the hyperglycemia-induced changes in these lenticular metabolite and enzyme-activity levels in the streptozocin-induced diabetic rat was examined to determine what, if any, relationship exists between these changes. Two weeks of untreated diabetes di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In other words, at the critical diameter, the cell is forced to take on a "cigar" geometry. The surface area of the cigar geometry is A = 7rDC + 7rDcLc, [1] whereas the volume of the cigar is V = 6 irDc' + 4-fL CD. [2] We now solve Eq.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, at the critical diameter, the cell is forced to take on a "cigar" geometry. The surface area of the cigar geometry is A = 7rDC + 7rDcLc, [1] whereas the volume of the cigar is V = 6 irDc' + 4-fL CD. [2] We now solve Eq.…”
Section: Appendixmentioning
confidence: 99%
“…A decrease in ouabain-sensitive Na',K+-ATPase (Na' pump, EC 3.6.1.37) activity has been found in diabetic lens, nerve, and glomerulus (1)(2)(3). This Na' pump impairment was corrected by aldose reductase inhibitors or by normalization of blood sugar with insulin.…”
mentioning
confidence: 99%
“…Although an increase of lens weight could indicate osmotic stress caused by polyol accumulation within lens tissue, the cataractogenic effects of CIG do not seem to be involved using the present approach. Despite the documented ability of the aldose reductase inhibitor SORB to effectively inhibit sugar-induced cataract formation in vivo (Kador et al, 1986;Yeh et al, 1987;Yeh and Ashton, 1990) and in vitro (Kador et al, 1986;Yeh et al, 1986), both in terms of adverse changes in lens weight and clarity and lenticular ATP and GSH content, SORB did not attenuate the toxicity of CIG to rat lenses either in terms of lens clarity or on the same biochemical markers of toxicity under the present culture conditions ( Table 2). The concentration of SORB used in this study was 5 times higher than the concentration that has been shown to effectively inhibit aldose reductase (Ͼ90%) and sorbitol accumulation (Ͼ80%) in rat lenses exposed to 35 mM glucose (Yeh et al, 1986).…”
Section: Discussionmentioning
confidence: 73%
“…In some cases, such as acetaminophen, the compound that penetrates the lens and causes the damage is a reactive metabolite that is formed via the cytochrome P450 system found in the ciliary body of the eye (Zhao and Shichi, 1995) or liver (Lubek et al, 1988). In other cases, such as S-(1,2-dichlorovinyl)-L-cysteine (Walsh Clang and Aleo, 1997), naphthalene (Lou et al, 1996), or glucose (Yeh et al, 1986(Yeh et al, , 1987Yeh and Ashton, 1990), the compound seems to require metabolic activation within the lens itself.…”
mentioning
confidence: 99%
“…• Reduction in cell-membrane phosphatidyl-inositol [7] leads to changes in membrane fluidity and a reduction in DAG production, which leads to reduction in protein kinase C activity. However, Yeh et al [27] found that the drug Sorbinil restores Na + /K + -ATPase activity at a lower concentration than that required for restoration of cell myo-inositol levels.…”
Section: Introductionmentioning
confidence: 99%